How can children of imprisoned parents in the UK be supported in school?. (2nd October 2022) - Shaw, Beth; Woods, Professor Kevin; Ford, Anne
ABSTRACT: If not supported appropriately, children of imprisoned parents face potential adverse outcomes, including difficulties with academic progress and mental health. This systematic literature review aims to explore ways in which children of imprisoned parents in the UK can be supported in school. Research databases and publication records from third sector organisations were searched. Eleven papers were included in the review and results highlighted a number of ways in which children of imprisoned parents can be supported in schools at a systemic, familial and individual level. Implications for schools, educational psychologists and future research are discussed.